Changement des espaces habitables, transformation de société et évolution des pratiques, cas d’étude : la vallée d'Oued Abdi - Saada, Asma; DEKOUMI, Djamel (Journal of Human Sciences, 2022)
The observation of the propagation, in Aurès, of small identical and self-built anarchic groups leading to transformations, especially in the architectural and urban aspect. New housing groups with new building materials appear almost everywhere on the landscape, thus expressing the changes in social structures. The objective of this study is to analyze this phenomenon of extensions. An investigative work effected in this area, in order to bring out various factors that influence this new urbanity, by trying to understand the relationships between the groups of this changing society and the spatial transformations of the traditional housing in this valley, in particular the living spaces. This approach leads to the well understanding of the strategies for the production of new type of living areas and houses, which reveal socio-economic mechanisms and structures as well as their transcriptions on the ground.